Promoting Child Growth and Development through the Mozaik Indonesia Radio Program at RRI Cirebon to Prevent Stunting: Edukasi Tumbuh Kembang Anak melalui Program Mozaik Indonesia di RRI Cirebon sebagai Strategi Pencegahan Stunting - KHOERIYAH, SALIS; monika, rika; Rosyad, Yafi Sabila; Kora, Firmina (Bhakti Sabha Nusantara, 2026)
Introduction: Stunting is a condition of growth failure in children under five resulting from chronic malnutrition and recurrent infections, particularly during the first 1,000 days of life. Low parental literacy regarding child growth and developmental indicators remains a major barrier to early stunting prevention efforts. Methods: This community service activity was conducted through an interactive dialogue between a child nursing expert and a radio broadcaster on the Mozaik Indonesia program aired by LPP RRI Cirebon. The educational approach included expert-led material presentations followed by live question-and-answer sessions with the audience. Results: The educational content covered stunting risk factors, physical characteristics of stunted children, and preventive strategies through balanced nutritional intake. The audience demonstrated high levels of engagement by actively participating via radio broadcasts and the comment section of RRI Cirebon’s YouTube channel, where various questions related to child growth and development were raised and addressed in real time. Conclusion: Radio broadcasting integrated with digital platforms such as YouTube has proven to be an effective and interactive medium for disseminating health information and reaching a broader community. Keywords: Stunting; Child Growth and Development; RRI Cirebon; YouTube; Health Education